Work Life Balance And Burnout For Sales Target Oriented Employees In Pekanbaru City - lamin, lamin (ADPEBI International Journal of Business and Social Science, 2022)
This study aims to determine the impact of work life balance and burnout on the performance of employees who are sales target-oriented in the city of Pekanbaru. In this study, data were collected through questionnaires to 100 sales force employees of the Automotive unit in Pekanbaru City. The data analysis technique used is multiple regression analysis which serves to prove the research hypothesis. Based on the value of t_count work life balance of 4.392 while for the value of t_table of 1.984 it can be concluded that work life balance has a significant effect on the performance of employees who are sales target-oriented in Pekanbaru city. Based on the t_count burnout value of 2.220 while the t_table value of 1.984 it can be concluded that the burnout variable has a significant effect on the performance of employees who are sales target-oriented in the city of Pekanbaru. Also the results of multiple regression can be concluded that the variables of Work life balance and Burnout together have a significant influence on employee performance variables in the city of Pekanbaru. The direction of the work life balance relationship on employee performance shows a positive relationship direction, the direction of the relationship between burnout and employee performance shows a negative relationship.